Specific gut microbiome signatures and the associated pro-inflamatory functions are linked to pediatric allergy and acquisition of immune tolerance - Francesca De Filippis; Lorella Paparo; Rita Nocerino; Giusy Della Gatta; Laura Carucci; Roberto Russo; Edoardo Pasolli; Danilo Ercolini; Roberto Berni Canani (Nature Communications, 2021)
Here, the authors profile the taxonomic composition and genetic potential of the gut microbiome of children with food or respiratory allergies and find that the gut metagenome of these patients is characterized by higher proinflammatory potential and reduced capacity of degrading complex polysaccharides, with Ruminococcus gnavus playing a central role.